The History of Al-Hirrah In the Light of The Writings of The German Orientalist Theodor Noldke (A Critical Analysis Study) - Hussein, Methaq Obais; Al-Taie, Osama Kadhim Omran (International Journal of Psychosocial Rehabilitation, 2020)
study is considered one of the important historical studies at all levels, for the scientific material that they presented which in turn is worthy to study especially these studies that concerned themselves with the history of ancient Arabs. The subject of our study that we are dealing with is one of them. These studies have shown many of the topics that Arab historians have omitted. Actually, these topics suffered from such neglecting because of lacking the temporal and spatial dimensions alike. So Noldka and his studies on this date are distinguished from others by his study that relied on various resources to reach the largest possible amount of truth.